Political Settlements and Development: Theory, Evidence, Implications - Tim Kelsall; Nicolai Schulz; William D. Ferguson; Matthias vom Hau; Sam Hickey; Brian Levy (Oxford University Press, 2022)
Few concepts have captured the imagination of the conflict and development communities in recent years as powerfully as the idea of a 'political settlement'. At its most ambitious, 'political settlements analysis' (PSA) promises to explain why conflicts occur and states collapse, the conditions for their successful rehabilitation, different developmental pathways from peace, and how to better fit development policy to country context. Yet despite the meteoric rise of the term and its tremendous promise, not all is well in the world of PSA. Rival definitions of the concept abound; there are disagreements about its scope and the way it should be used; a growing schism between conflict specialists and economists; basic concepts are ambiguous; and little progress has been made on measurement. This book consequently has three main aims. The first is to argue for a revised definition of a political settlement, capable of unifying its diverse strands. The second is to put the concept on a more solid theoretical and scientific footing, providing a method for measuring and categorizing political settlements, using both qualitative case studies and a large-n statistical analysis to illustrate its potential. And the third is to examine the implications of the findings for mainstream social science analysis and for policymakers.
Keywords: 320; Government Policy; Provision and Effects of Welfare Programmes; Economic Development; Development Planning and Policy; Rent-Seeking; Lobbying; Elections; Legislatures; and Voting Behavior; Bureaucracy; Administrative Processes in Public Organizations; Corruption; Conflict; Conflict Resolution; Alliances; Revolutions; Positive Analysis of Policy Formulation and Implementation; Political Economy